Value Chain Alliance and Financing of Sikki Craft in Nepal - Bhandari, Padam Lal; Kattel, Rishi Ram; Thapa, Yam Bahadur; Baral, Rudra (International Journal of Social Sciences and Management, 2020)
This paper examines the value chain alliance and financing of sikki craft in Nepal. Among other crafts, sikki crafts is the potential handicrafts in rural community in Nepal. Sikki (dhakiya) is the natural fiber made from grass and which is being used among Tharu communities as a gift during marriage ceremony of daughter and high export potential in global market. Sikki is more labor-intensive based production, which involvement of women in whole process as well as 79% costs of raw materials have been used from local resources. Lack of awareness, inadequate design, lack of coordination, networking and structures, inadequate business knowledge and inefficient technology were major constraints hindering the growth of this sikki craft sub-sector in Nepal. It was estimated that a total of 630 enterprises can be developed during the five-year period. The study revealed that, a total of NPR 70.5 million will required to manage their enterprises that can create over 1260 jobs. The loan fund to be required from external financial institutions will be NPR 3.9 million, where Government of Nepal can play a catalytic role to help these entrepreneurs obtain such loans from the formal sources through brokerage system charging fees. The return of investment of this product was 66% and benefit-cost ratio was 1.7. From the points of view of value chain financing of sikki craft, the business seems viable to the rural women in Terai’ community of Nepal from employment generation and promotion of Nepalese handicraft in global niche markets. Int. J. Soc. Sc. Manage. Vol. 7, Issue-3: 131-151